Convergence for Hyperbolic Singular Perturbation of Integrodifferential Equations. (2nd August 2007) - Liang, Jin; Liu, James; Xiao, Ti-Jun
Abstract : By virtue of an operator-theoretical approach, we deal with hyperbolic singular perturbation problems for integrodifferential equations. New convergence theorems for such singular perturbation problems are obtained, which generalize some previous results by Fattorini (1987) and Liu (1993).